Atypical dissemination of lung cancer to the adrenal gland and to the spleen - Chorąży, Marek; Majcher, Marta; Fedyszyn-Urbanowicz, Katarzyna; Bierzyńska-Macyszyn, Grażyna; Kwiatkowski, Robert (Contemporary Oncology/Współczesna Onkologia, 2012)
Metastases of lung cancer to such organs as the liver, bones or to the central nervous system appear to be a frequent complication of this disease. At the same time, metastases to the adrenal gland are found less frequently. Metastases of lung cancer to the spleen are a great rarity and they are described sporadically. Our report presents a unique case of left lung cancer with simultaneous metastases to the adrenal gland and to the spleen. All the presented lesions were diagnosed by ultrasound guided biopsy and confirmed by histopathological examination.